Association between recent methamphetamine use, antiretroviral therapy and HIV viral load; a mediation analysis from a cohort of HIV positive persons who inject drugs in Hai Phong, Vietnam. (March 2023) - Feelemyer, Jonathan; Des Jarlais, Don; Nagot, Nicolas; Duong Thi, Huong; Thi Hai, Oanh Khuat; Pham Minh, Khuê; Hoang Thi, Giang; Nham Thi Tuyet, Thanh; Cleland, Charles M; Arasteh, Kamyar; Caniglia, Ellen; Chen, Yu; et al.
Background: There has been a significant increase in methamphetamine use among persons who use drugs in Vietnam in the last 5–10 years. We examined the degree to which adherence to antiretroviral therapy (ART) mediates the relationship between recent methamphetamine use and unsuppressed HIV viral load among people who inject drugs (PWID) in Hai Phong, Vietnam. Methods: We recruited PWID from October 2016-October 2018 and enrolled HIV positive PWID into a cohort, with up to three years of total follow-up. We assessed relationships among recent methamphetamine use frequency, ART adherence and unsuppressed HIV viral load. Mediation analysis was used to estimate the total and natural direct effects of recent methamphetamine use on unsuppressed HIV viral load and the indirect effect proportion. Results: We enrolled 792 HIV seropositive PWID into the cohort; approximately 75.9% reported high/perfect ART adherence at baseline and 81.3% were virally suppressed. In mediation analysis, the total effect for the association between methamphetamine use and unsuppressed HIV viral load (1000 copies/mL) was 3.94 (95% CI: 1.95, 7.96); the natural direct effect was 2.14 (95% CI: 1.29, 3.55); the proportion mediated by self-reported ART adherence was 0.444. Similar results were found when examining lower unsuppressed HIV viral load cutpoints of 250 copies/mL and 500 copies/mL. Conclusions: Methamphetamine use is associated with unsuppressed HIV viral load among PWID despite high levels of ART adherence. Further research is needed to better understand these relationships, with emphasis on potential biological pathways that may interact with ART.